A novel optical ammonia sensor based on reflectance measurements for highly polluted and coloured water - Tan L.L.; Ahmad M.; Lee Y.H. (2024)
One of the major problems in the analysis of ammonia (NH 3) using spectrophotometric method is highly coloured water sample. A reflectometric NH 3 sensor based on a facile single-step immobilisation of cobalt(II) (Co 2+) ion onto high capacity Dowex HCR-W2 microspheres has been developed to enable the direct NH 3 determination in highly coloured water samples. The combination of Co 2+ ion-immobilised microspheres via cation exchange chemical reaction and reflectometric technique has improved the optode sensing performance with respect to linear response range and response time. Immobilised Co 2+ ion, when complexed with NH 3 gave a blue colouration of hexamminecobaltate(II) ([Co(NH 3) 6] 2+) complex at pH 13. The NH 3 sensor reached maximum colour intensity in ?6 min at ambient conditions. The linear calibration curve was 60-290 mM NH 3 with a detection limit of 16 mM NH 3, which is suitable for direct determination of NH 3-enriched leachate water samples. A good reproducibility between 5.4 and 5.9% relative standard deviation (RSD) was obtained with the probe and the sensing performance can be regenerated using buffer pH 1. The effect of potential interference ions has been investigated during the quantification of NH 3 in heavily polluted sewage water. The results obtained were in good agreement with those produced by acidimetric reference method.